An evaluation of the challenges faced by rural-based small, micro and medium enterprises in Pietermaritzburg, South Africa. - Nxaba, Siphosenkosi Blessing (My University, 2014)
Small, Micro and Medium Enterprises (SMMEs) in the South African present context are integral instruments of economic and social development. In these times of high unemployment in South Africa, the need for SMMEs to alleviate the high rate of poverty due to unemployment is evident. The government is committed to ensure that small businesses progressively increase their contribution growth and performance of the South African economy in critical areas such as job creation, equity and access to markets. As from 1994, with the new advent of a new democratic era, government has taken measures to ensure that small business development becomes a key focus. Since then, government has put in place institutions and programmes within all three tiers of government with the aim of providing comprehensive support to small business. This is suggestive of the government being mindful of the challenges/gaps which still need to be addressed to support small business especially in rural areas where unemployment and poverty are rife. Whilst there are institutions which provide support to SMMEs, the overall impact of these initiatives is insignificant. This study explored the perceptions of the owners of rural-based SMMEs about factors responsible for the success and failure of rural-based SMMEs. The study adopted a qualitative approach and it was exploratory in nature. Semi-structured interviews were conducted with five owners of rural-based SMMEs and with three key informants from three local municipal districts/offices around Pietermaritzburg in KZN. The main findings of the study identified initiatives to address the challenges to rural-based SMMEs, such as, provision of good infrastructure, business management skills, business equipment and land/premises. The recommendations suggested a need of partnerships between banks and community business support organizations, subcontracting of SMMEs to big business, introducing entrepreneurship from school level and introducing monitoring and evaluation systems in all government levels as proposals to address challenges to rural-based SMMEs.
Keywords: Entrepreneurship; Small, Micro and Medium Enterprises (SMMEs); Poverty alleviation; Rural development; Economic development